A 2000-year lipid biomarker record preserved in a stalagmite from north-west Scotland - Blyth, Alison; Baker, A.; Thomas, L.; Van Calsteren, P. (John Wiley & Sons, 2011)
Previous studies on lipid biomarkers preserved in Chinese stalagmites have indicated that ratios of low-molecular-weight (LMW) to high-molecular-weight (HMW) n-alkanes, n-alkan-2-ones, n-alkanols and n-alkanoic acids can be used as an index of vegetation versus microbial organic matter input to the system and, by extension, a marker of climatic changes, with increases in the proportion of LMW compounds coinciding with colder periods. Here we test whether this hypothesis is equally applicable to a different geographical region (north-west Scotland), by examining a stalagmite record of the past 200 years, and a wider range of lipid markers. We also test the applicability of other lipid proxies in this context, including the use of n-alkane ratios, to interpret vegetation changes, and unsaturated alkanoic acid ratios as climatic indicators. The results show that lipid proxies preserved in stalagmites, andespecially those related to vegetation, are potentially extremely useful in palaeoenvironmental research. Of particular value is the use of C27/C31 n-alkane ratios as a proxy for vegetation change, clearly indicating variations between herbaceous and arboreal cover. This proxy has now been successfully applied to samples from diverse environments, and can be considered sufficiently robust to be of usein analysing future stalagmite records. It will be of particular value in areas where reliable pollen records are not available, as is often the case with deeper cave deposits. However, the division between LMW and HMW aliphatic compounds is not a clear-cut case of microbial versus plant activity, with the changes in LMW compounds relating more closely to those in their HMW analogues than in specific bacterial biomarkers. The use of unsaturated alkanoic acid ratios here gives conflicting results, with the observed variation through time depending on the isomer measured.The discrepancies between the findings of this study and previous work are likely to be due to the varying controls on the lipids (original organic matter input, and compound degradation), which in turn will be affected by whether the main climatic limiting factor on the soil is temperature or precipitation. This suggests that lipid proxies preserved in stalagmites must be interpreted with care, particularly in the case of bacterial compounds which may be derived from within the cave or from the soil. However, many of these issues can be resolved by the use of multi-proxy studies.